An overview of the distribution, status and behavioural ecology of White-shouldered Ibis in East Kalimantan, Indonesia - Sozer, Resit; Annemarie, J W; van der Heijden, J (KUKILA, 1997)
An overview is presented of recent observations of the White shouldered Ibis Pseudibis davisoni in East Kalimantan, Indonesia. 45 encounters were made, while only 19 previous records were known from the island of Borneo. In total, 142 individual birds were sighted, of which 134 date from the three years 1994 1997. This high number of sightings is explained by multiple sightings of the same birds. The formerly known distribution of the species is expanded, and probable sub adult specimens and copulation have been observed. Considering the paucity of knowledge and the 'endangered' status, these sightings may be of great importance for the conservation of the species.